1999
DOI: 10.1111/1475-4983.00112
|View full text |Cite
|
Sign up to set email alerts
|

New Genera and Species of Psychodoid Flies from the Lower Cretaceous Amber Lebanon

Abstract: Until now, only two Psychodoidea were known from Lebanese amber. We describe two new genera and species of Phlebotomidae (Mesophlebotomites hennigi gen. et sp. nov., Libanophlebotomus lutfallahi gen. et sp. nov.) and four new genera with six new species of Psychodidae (Paleopsychoda solignaci gen. et sp. nov., Paleopsychoda jacquelinae sp. nov., Protopsychoda nadiae gen. et sp. nov., Protopsychoda hammanaensis sp. nov., Libanopsychoda abillamai gen. et sp. nov., Cretapsychoda inexpectata gen. et sp. nov.) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 4 publications
1
34
0
1
Order By: Relevance
“…A minimum date of 100 million years can be established from actual fossils in Early Cretaceous Myanmar amber. However, the fossil record of sand flies extends back to 125 million year Early Cretaceous Lebanese amber [52], although some suspect that sand flies existed in the Jurassic [53] or even in the Triassic [54].…”
Section: 3mentioning
confidence: 99%
“…A minimum date of 100 million years can be established from actual fossils in Early Cretaceous Myanmar amber. However, the fossil record of sand flies extends back to 125 million year Early Cretaceous Lebanese amber [52], although some suspect that sand flies existed in the Jurassic [53] or even in the Triassic [54].…”
Section: 3mentioning
confidence: 99%
“…Therefore a study of the fossil psychodoid flies is of great importance for highlighting the real evolution and phylogeny of this group. Azar et al (1999) demonstrated that the addition of fossil psychodoid flies to the phylogeny based on recent taxa does not disturb its topology, but could be a test of the historical value of the phylogeny through the character homoplasy. Moreover, the addition of the fossil taxa demonstrates that the phylogenetical history of Psychodoidea is clearly more complicated than suggested by the study of the recent taxa alone.…”
Section: Importance Of Phylogenetic Analysis and Fossil Studymentioning
confidence: 99%
“…The knowledge of fossil taxa has greatly improved up to least 30 genera and more than 75 species since the works of Ansorge (1994), Azar et al (1999), Azar and Nel (2002), Nel et al (2002). Lambrecht (1980) estimated that the psychodoids originated as long ago as the Permian/Triassic boundary.…”
Section: Importance Of Phylogenetic Analysis and Fossil Studymentioning
confidence: 99%
“…Both Phlebotomites brevifilis and P. longifilis were described by Hennig, in 1972, and more recently M. hennigi and L. lutfallahi by Azar et al (1999) from the Lower Cretaceous Lebanon. There are one record of ancestral members of the living genus Phlebotomus, P. pungens (Loew, 1845) probably from the Holocene and Sergentomyia from the Eocene (Stuckenberg 1975) .…”
mentioning
confidence: 92%